Little fox in the snow - London, Jonathan, 1947- (Candlewick Press, 2018)
"A red fox emerges from its burrow one wintry morning, a fiery streak against stark white surroundings, driven by hunger and curiosity to investigate its world. Encountering a mouse, a hare, and a wolverine, the little fox takes on the role of both hunter and hunted before returning to the safety of its den, where- perhaps- it dreams of something more. Jonathan London's poetic text and Daniel Miyares's stunning impressionistic paintings provide an evocative portrait of a fox and its place in the natural world." -- Provided by publisher.